MANAJEMEN PEMELIHARAAN MESIN BUBUT DALAM MENJAMIN KEBERLANJUTAN PROSES PEMBELAJARAN PADA JURUSAN TEKNIK PEMESINAN SMK NEGERI 1 NGLIPAR GUNUNGKIDUL - Wuri Damayanti; Saryanto; Jumintono (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: This study aims to describe the management of lathe machine maintenance in ensuring the sustainability of the learning process in the Machining Engineering Department at SMK Negeri 1 Nglipar. The study employed a descriptive qualitative approach with data collection techniques consisting of interviews, observations, and documentation. The research informants included the principal, the head of the Machining Engineering program, and students. The results of the study indicate that lathe machine maintenance is carried out through three stages, namely routine maintenance, periodic maintenance, and incidental maintenance. Routine maintenance is conducted after every practical session by students through cleaning the machines and work areas. Periodic maintenance is performed by the toolman through scheduled inspections of oil and machine components, while incidental maintenance is conducted when unexpected machine damage occurs. Maintenance financing is planned through BOS funds and support from the school committee. The school also implements a strategy of independently manufacturing machine components to overcome the high cost of original spare parts. The challenges faced include the limited number of machines, high maintenance costs, and unpredictable machine damage. Nevertheless, the maintenance management implemented has been able to sustain practical learning activities so that the learning process can continue effectively. Keywords: Maintenance Management, Lathe, Machining Engineering, Vocational High School   Abstrak: Penelitian ini bertujuan untuk mendeskripsikan manajemen pemeliharaan mesin bubut dalam menjamin keberlanjutan proses pembelajaran pada Jurusan Teknik Pemesinan SMK Negeri 1 Nglipar Gunungkidul. Penelitian menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data berupa wawancara, observasi, dan dokumentasi. Informan penelitian terdiri atas kepala sekolah, kepala program keahlian Teknik Pemesinan, dan peserta didik. Hasil penelitian menunjukkan bahwa pemeliharaan mesin bubut dilakukan melalui tiga tahapan, yaitu perawatan rutin, perawatan berkala, dan perawatan insidental. Pemeliharaan rutin dilaksanakan setiap selesai praktik oleh siswa dengan membersihkan mesin dan area kerja. Pemeliharaan berkala dilakukan oleh toolman melalui pengecekan oli dan komponen mesin secara terjadwal. Sedangkan pemeliharaan insidental dilakukan ketika terjadi kerusakan mendadak pada mesin. Perencanaan pembiayaan pemeliharaan bersumber dari dana BOS dan dukungan komite sekolah. Sekolah juga menerapkan strategi pembuatan komponen secara mandiri untuk mengatasi mahalnya spare part original. Kendala yang dihadapi meliputi keterbatasan jumlah mesin, tingginya biaya perawatan, serta kerusakan yang tidak terprediksi. Meskipun demikian, manajemen pemeliharaan yang dilakukan mampu menjaga keberlanjutan pembelajaran praktik sehingga proses pembelajaran tetap berjalan secara efektif. Kata Kunci: Manajemen pemeliharaan, Mesin bubut, Teknik pemesinan, SMK.